Correlation Between THSD7A Expression and Tumor Characteristics of Azoxymethane-Induced Colon Cancer Model in Rats - Aktepe, Oktay Halit; Sahin, Taha Koray; Guner, Gurkan; Guven, Deniz Can; Yeter, Haci Hasan; Kurtulan, Olcay; Ozercan, Ibrahim Hanifi; Dizdar, Omer; Yalcin, Suayib (Turkish Journal of Gastroenterology, 2021)
Background: Thrombospondin type 1 domain-containing 7A (THSD7A) has emerged as a new potential molecular tool for multipletumors since that THSD7A was detected to be expressed in various malignant tumor types including colorectal cancer (CRC). Thus, weinvestigated the correlation between THSD7A expression and pathologic determinants of azoxymethane (AOM)-induced CRC in a ratmodel.Methods: A total of 30 rats were included in the study (experimental group; n = 15, control group; n = 15). Azoxymethane was administered to the experimental group weekly as subcutaneous injections at a dose of 15 mg/kg bodyweight for 3 weeks. Five months later,42 tumors were obtained in the study group and histopathologic evaluation of CRC tumors for THSD7A was performed by immunohistochemical staining. Thrombospondin type 1 domain-containing 7A expression was classified according to staining levels.Results: While 28.6% of the colonic tumors were stained as negative, mild-moderate and strong staining was determined in 61.9% and9.5% of the tumors, respectively. Thrombospondin type 1 domain-containing 7A expression levels inversely correlated with Ki-67 expression (P < .001) and tumor grade (P =.02). Receiver operating characteristic analysis showed Ki-67 staining ≥20.5% was determinedas a cut-off value for negatively stained THSD7A tumors with 91% sensitivity and 69% specificity (P = .001, area under curve: 0.822).Moreover, higher Ki-67 expression was found to be associated with higher tumor grade (P < .001), presence of lymphatic invasion(P = .003), and higher T stage (P = .003).Conclusion: Negative staining for THSD7A seems to be linked to invasive pathologic determinants in AOM-induced CRC in rats